2018
DOI: 10.1016/j.biortech.2018.01.111
|View full text |Cite
|
Sign up to set email alerts
|

Assimilable organic carbon (AOC) variation in reclaimed water: Insight on biological stability evaluation and control for sustainable water reuse

Abstract: This review highlights the importance of conducting biological stability evaluation due to water reuse progression. Specifically, assimilable organic carbon (AOC) has been identified as a practical indicator for microbial occurrence and regrowth which ultimately influence biological stability. Newly modified AOC bioassays aimed for reclaimed water are introduced. Since elevated AOC levels are often detected after tertiary treatment, the review emphasizes that actions can be taken to either limit AOC levels pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The AOC is usually considered as one of the main indicators of biological water stability and is a critical parameter for drinking water treatment and distribution processes[ 4 , 5 ]. Recently, the AOC concept has also been extended to measure microbial growth potential for environmental samples such as soil water extracts [ 6 8 ], seawater [ 9 11 ] and reclaimed water[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AOC is usually considered as one of the main indicators of biological water stability and is a critical parameter for drinking water treatment and distribution processes[ 4 , 5 ]. Recently, the AOC concept has also been extended to measure microbial growth potential for environmental samples such as soil water extracts [ 6 8 ], seawater [ 9 11 ] and reclaimed water[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EPS released by attached bacteria can cause buildup of head loss of the filters and increase of DBP formation [27]. In addition, the detachment of accumulated bacteria can increase the bacterial concentration in the effluent [65,66]. Although these microbes can be easily disinfected by post-chlorination, some bacteria attached to GAC particles can be resistant to disinfectants [65,67].…”
Section: Filling Materials (Media)mentioning
confidence: 99%
“…AOC is a useful indicator of biostability of drinking water, but it cannot give information about biological instability caused by growth of pathogenic bacteria and autotrophic bacteria [10]. Further study is needed to investigate bacterial community composition of biofilm in biological filters and distribution system.…”
Section: Effects Of Advanced Treatment On the Biostability Of Drinkinmentioning
confidence: 99%
“…The other parameter is assimilable organic carbon (AOC) which is easily available organic substrates and can be converted to bacterial biomass [8]. AOC is considered as a better indicator of bacterial regrowth potential of drinking water because the bioassay can directly measure the newly formed bacterial biomass as a result of BOM assimilation in water, and it is very sensitive with the low detection limit of 10 μg/L [6,7,[9][10][11]. Many studies have suggested various criteria for biostability of drinking water in distribution systems based on the AOC concentrations.…”
Section: Introductionmentioning
confidence: 99%